2019
DOI: 10.3390/ma12060986
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dopant Distribution in Yttrium-Doped Bioactive Glass for Selective Internal Radiotherapy Applications Using Spray Pyrolysis

Abstract: In this study, we demonstrate the fabrication of Y-doped bioactive glass (BG), which is proposed as a potential material for selective internal radiotherapy applications. Owing to its superior bioactivity and biodegradability, it overcomes the problem of yttrium aluminosilicate spheres that remain in the host body for a long duration after treatment. The preparation of Y-doped BG powders were carried out using a spray pyrolysis method. By using two different yttrium sources, we examine the change of the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Therefore, the hollow structure is formed once the temperature reached the decomposition temperature of PEG (450 °C) [20]. To note, the calcination temperature of BG is 550 °C [21], which allows the decomposition of PEG to complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hollow structure is formed once the temperature reached the decomposition temperature of PEG (450 °C) [20]. To note, the calcination temperature of BG is 550 °C [21], which allows the decomposition of PEG to complete.…”
Section: Discussionmentioning
confidence: 99%
“…It is a highly hydrophilic polymer, which is soluble in BG precursor’s solution including water and ethanol solvent [19]. Furthermore, its decomposition temperature (450 °C) [20] is much lower than the calcination temperature of BG (550 °C) [21], which allows the decomposition reaction of PEG to complete.…”
Section: Introductionmentioning
confidence: 99%
“…The additive manufacturing brings high degrees of geometrical freedom to the production of alloy components [91]. The advantages of the additive manufacturing, such as customized geometry [92], fast cooling for intermediate phase effects [93], mixing of metallics-ceramics powders [94,95], and anisotropic effects [96], are well known. For additive manufacturing, high-entropy alloys also show great potentials [97][98][99][100].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…In addition, Y-doped BGs have also exhibited bioactive behavior. Tesfay et al [ 105 ], for example, observed that Y-containing 58S BG led to rapid apatite-like formation after 6 h in SBF. Recent work has also shown that replacing B 2 O 3 with 1 wt.% Y 2 O 3 in the glass composition 53 B 2 O 3 –20 CaO–12 K 2 O–6 Na 2 O–5 MgO–4 P 2 O 5 (wt.%) had a greater effect on the proliferation and migration of adipose stem cells (ASCs) in an α-minimal essential medium in vitro [ 114 ].…”
Section: Rare Earth Elements-containing Bioactive Glassesmentioning
confidence: 99%